Man in the media technology industry - Gazniuk, L.; Dyachenko, Ya.; Kovalenko, Ju.; Semenova, Yu.; Fedorenko, O. I.; Федоренко, О. І.; Федоренко Олена (Man. Society. Communication: International scientific and practical conference (Veliky Novgorod, 23-24 April 2020) / European Proceedings of Social and Behavioural Sciences. - Veliky Novgorod, 2021. - Vol. 108. - P. 618-623, 2021)
У статті показано, що сучасне медіасередовище є якісно новий етап трансформації медіасреди, оскільки відбувається не тільки інтенсифікація рівня розвитку науки і технологій, нових структур суспільного життя і способів організації виробництва, а й також формування нових форм соціальності, розуміння природи людини і його трансформація. Проаналізовано вплив медіа-технологій на соціальне середовище і показано, що розробки в області нанотехнологій, робототехніки, мемрісторной електроніки, що пронизують всі рівні живої і неживої матерії, стають глобальними загрозами. Технології NBICS задають нову стратегію розвитку цивілізації, і їх потенційні наслідки вимагають гуманітарного осмислення як перспектив, так і загроз її реалізації. Сама людина стає свідком нового еволюційного стану цивілізації і трансформується під впливом комплексу сучасних медіа-технологій. Доведено, що медіа-технології змінюють повсякденне життя людей, їх спілкування, спосіб їх безпосереднього особистого буття, а світ людини під впливом медіа-технологій, медіасоціума і медіакультури трансформується в його Медіасвіт. Розкрито соціогуманітарна функціональність цифрових медіа-мереж як цифрових посередників і охарактеризовано їх вплив на соціально-природне середовище проживання людини.

The article shows that the modern media environment is a qualitatively new stage in the transformation of the media environment, since there is not only an intensification of the level of development of science and technology, new structures of social life and ways of organizing production, but also the formation of new forms of sociality, understanding of human nature and his transformation. The influence of media technologies on the social environment is analyzed and it is shown that developments in the field of nanotechnology, robotics, memristor electronics, which penetrate all levels of living and non-living matter, become global threats. NBICS technologies set a new strategy for the development of civilization, and their potential consequences require a humanitarian reflection on both the prospects and the threats to its implementation. A human himself becomes a witness to a new evolutionary state of civilization and is transformed under the influence of a complex of modern media technologies. It is proved that media technologies are changing the everyday life of people, their communication, the way of their direct personal being, and the human world under the influence of media technologies, media socium and media culture is transformed into his media world. The socio-humanitarian functionality of digital media networks as digital mediators is revealed and their influence on the social-natural environment of human habitation is characterized.

В статье показано, что современная медиасреда представляет собой качественно новый этап трансформации медиасреды, поскольку происходит не только интенсификация уровня развития науки и технологий, новых структур общественной жизни и способов организации производства, но и также формирование новых форм социальности, понимание природы человека и его трансформация. Проанализировано влияние медиа-технологий на социальную среду и показано, что разработки в области нанотехнологий, робототехники, мемристорной электроники, пронизывающие все уровни живой и неживой материи, становятся глобальными угрозами. Технологии NBICS задают новую стратегию развития цивилизации, и их потенциальные последствия требуют гуманитарного осмысления как перспектив, так и угроз ее реализации. Сам человек становится свидетелем нового эволюционного состояния цивилизации и трансформируется под воздействием комплекса современных медиа-технологий. Доказано, что медиа-технологии меняют повседневную жизнь людей, их общение, способ их непосредственного личного бытия, а мир человека под влиянием медиа-технологий, медиасоциума и медиакультуры трансформируется в его медиамир. Раскрыта социогуманитарная функциональность цифровых медиа-сетей как цифровых посредников и охарактеризовано их влияние на социально-природную среду обитания человека.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u Scopus; human media network transformation; media technology; media technology industry; media technology revolution; posthuman; трансформація мережі людських медіа; медіа-технології; індустрія медіа-технологій; трансформация человеческих медиа-сетей; медиа-технологии; индустрия медиа-технологий; постчеловек; постлюдина